Forgotten or unpromising? The elusive phenomenon of under-aided countries, sectors and sub-national regions - Elena Pietschmann (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
The existence of under-aided countries, sectors, and sub-national regions – also known as “aid orphans” – implies inefficiencies in the current overall allocation of aid resources. This is of particular concern because aid effectiveness depends not only on how well resources are utilised, but also on how efficiently they are allocated across recipients and uses. Different conceptual approaches to aid allocation, as well as spillovers across countries and sectors, make it difficult to define an “optimal allocation” and thus to pin down the criteria for identifying cases of “insufficient aid”. Nevertheless, it is possible to identify countries whose aid receipts are considerably lower than others with similar characteristics, as well as sectors that receive insufficient aid while donors crowd in other areas. Donor coordination and transparency in aid allocations are crucial for addressing the problem and achieving a more efficient allocation of resources
Keywords: 330; Armut und Ungleichheit; Entwicklungsfinanzierung und öffentliche Finanzen; Sicherheit; Frieden und fragile Staaten; Wirksamkeit und Evaluierung; Entwicklungshilfe; Allokationseffizienz; Branche; Strukturschwache Region; Informationsverbreitung; Welt; Entwicklungsländer; Industrieländer